2016
DOI: 10.2119/molmed.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Proteinase 3 Contributes to Nonalcoholic Fatty Liver Disease and Insulin Resistance

Abstract: Activation of inflammatory pathways is known to accompany development of obesity-induced nonalcoholic fatty liver disease (NAFLD), insulin resistance and type 2 diabetes. In addition to caspase-1, the neutrophil serine proteases proteinase 3, neutrophil elastase and cathepsin G are able to process the inactive proinflammatory mediators interleukin (IL)-1β and IL-18 to their bioactive forms, thereby regulating inflammatory responses. In this study, we investigated whether proteinase 3 is involved in obesity-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
0
29
0
3
Order By: Relevance
“…Disorder of lipid metabolism is a fundamentally pathological conditions in the development of insulin resistance and type 2 diabetes [7]. For instance, lipid accumulation in insulin-target tissues such as liver and muscle contributes to reduction of insulin signaling [42,43]. Previous studies have shown that Lycopene inhibited the pathogenesis of hepatic steatosis [16,31].…”
Section: Discussionmentioning
confidence: 99%
“…Disorder of lipid metabolism is a fundamentally pathological conditions in the development of insulin resistance and type 2 diabetes [7]. For instance, lipid accumulation in insulin-target tissues such as liver and muscle contributes to reduction of insulin signaling [42,43]. Previous studies have shown that Lycopene inhibited the pathogenesis of hepatic steatosis [16,31].…”
Section: Discussionmentioning
confidence: 99%
“…Also, NE knockout mice have been described to have higher energy expenditure rates, increased body temperature, and increased fatty acid oxidation [16]. In line with these results, PR3/NE knockout mice gained less weight, accumulated less triglycerides in the liver than WT mice fed a HFD, and have decreased mRNA expression of gene-encoding proteins involved in lipogenesis and fatty acid uptake, suggesting a better metabolic profile than WT mice [18]. Since our mouse model is lacking all the genes mentioned above, it is likely that these mice have also a more active basal metabolism and have an improved control of lipid metabolism than WT mice.…”
Section: Discussionmentioning
confidence: 60%
“…Our group has previously shown that double knockout mice deficient in NE/PR3 do gain weight after HFD intervention and showed a certain degree of liver steatosis but significantly less than WT controls fed the same diet. In addition, these mice were protected against the development of adipose tissue inflammation [18]. In contrast, Dixon et al showed that Caspase-1/11 double knockout mice developed HFD- Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Their main metabolic functions included lipid and glucose metabolism, transport/metabolism of vitamins and minerals, immune system function, blood clotting, and acute phase reactions (Bisoendial et al, 2015;Calder et al, 2013;Campenhout, Campenhout, & Lagrou, 2003;Carter & Worwood, 2007;Clerc et al, 2016;Dabrowska, Tarach Toonen et al, 2016;UniProt, 2016UniProt, , 2017aUniProt, , 2017bWalldius & Jungner, 2004;Wang et al, 2015;Wu & Lyons, 2011). Their main metabolic functions included lipid and glucose metabolism, transport/metabolism of vitamins and minerals, immune system function, blood clotting, and acute phase reactions (Bisoendial et al, 2015;Calder et al, 2013;Campenhout, Campenhout, & Lagrou, 2003;Carter & Worwood, 2007;Clerc et al, 2016;Dabrowska, Tarach Toonen et al, 2016;UniProt, 2016UniProt, , 2017aUniProt, , 2017bWalldius & Jungner, 2004;Wang et al, 2015;Wu & Lyons, 2011).…”
Section: Discussionmentioning
confidence: 99%